KARAKTERISTIK PENDERITA KISTA OVARIUM YANG DIRAWAT INAP DI RUMAH SAKIT ST ELISABETH MEDAN TAHUN 2008 - 2012 - Dumaris Siringo-ringo; hiswani .; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Ovarian cyst is one of the gynecological benign tumor most often found in women in the reproductive life. Most of the cysts are formed due to changes in hormone levels that occur during the menstrual cycle, the production and release of eggs from the ovaries. The incidence of ovarian cyst disease in Indonesia is not yet known with certainty because the recording and reporting unfavorable. As an illustration in the hospital. Dharmais cancer was found about 30 patients each year. At RSUP H. Adam Malik Medan are the total number of patients with ovarian cysts in 2008-2009 as many as 47 people. General Hospital Medan Dr.Pirngadi Januari - October 2010 ovarian cysts sufferers in women of childbearing age totaling 34 people. To determine the characteristics of patients with ovarian cysts who are hospitalized at St. Elisabeth Hospital Medan in 2008 - 2012 was a descriptive study, with case series design. Population and samples of data 116 patients (total sampling). Data were analyzed by chi-square test, Fisher Exact, and T-test. The research found ovarian cysts proportion of patients: age 29-37 years (29.7%), Batak (80.2%), Protestant (56.9%), education Colleges / Universities (47.4%) , occupation Housewife (33.6%), marital status (71.6%), benign ovarian cysts (94.8%), the size of the cyst diameter 3.83 to 7.52 cm (40.5%), pain lower abdomen (67.7%), still menstruating (87.9%), surgical treatment (68.1%), the average treatment length 6.01 (6 days), outpatient home (95.7%). There is a significant difference in the proportion of types of cysts by age (p = 0.012), chi-square test can not be performed to determine the proportion of the size of the cyst is based on complaints because there are 4 cells (66.7%) who had expected count <5, there is no significant difference in the proportion of the diameter of the cyst by cyst type (p = 0.400), chi-square test can not be performed to determine the proportion of the diameter of the cyst by level of education because there are 4 cells (50.0%) having an expected count <5, there is a significant difference between the average long maintainability based medical management (p = 0.001), there is no significant difference in the proportion of state while returning by type of cysts (p = 0.237). Expected for the hospital St. Elisabeth Medan field in order to improve and maintain the quality of care of patients with ovarian cysts and ovarian cysts sufferers complete recording of such parity, history of the use of contraceptives. Keywords: Ovarian Cyst, patient characteristics, RS St. Elisabeth Medan 2008-2012, Case Series